Hormonal therapy with letrozole for relapsed epithelial ovarian cancer: Long-term results of a phase II study - Papadimitriou, C.A.; Markaki, S.; Siapkaras, J.; Vlachos, G.; Efstathiou, E.; Grimani, I.; Hamilos, G.; Zorzou, M.; Dimopoulos, M.-A. (Oncology, 2004)
Objective: We conducted a phase II trial to evaluate the activity of oral letrozole in women with relapsed or recurrent epithelial ovarian cancer. Methods: Twenty-seven patients were treated with letrozole at a dose of 2.5 mg once a day. Patients with measurable or evaluable disease (n = 21) and those with only increasing CA 125 serum levels (n = 6) were eligible. Paraffin-fixed histological sections from tumor specimens resected at the initial laparotomy were assessed for the presence of estrogen, and progesterone receptors. Results: Among the 21 patients with measurable or evaluable disease who were evaluated for response by WHO criteria, we observed one complete and two partial responses for an objective response rate of 15%. Using criteria for CA 125 response we obtained a marker response in 4 of 27 patients (15%), and the marker remained stable in 5 additional patients (18%). Letrozole treatment was generally well tolerated. No correlation was observed between tumor marker response or stabilization and either estrogen or progesterone receptor expression. Conclusion: The results of our study suggest that the aromatase inhibitor letrozole is an agent with some activity and limited toxicity for relapsed ovarian cancer. As we could not find any association between response and hormonal receptor expression, the underlying mechanisms of letrozole action have to be elucidated. Copyright © 2004 S. Karger AG, Basel.
Keywords: Letrozole; Ovarian cancer hormonal therapy